You can Download Samacheer Kalvi 12th Maths Book Solutions Guide Pdf, Tamilnadu State Board help you to revise the complete Syllabus and score more marks in your examinations.

## Tamilnadu Samacheer Kalvi 12th Maths Solutions Chapter 3 Theory of Equations Ex 3.4

Question 1.

Solve:

(i) (x – 5) (x – 7) (x + 6) (x + 4) = 504

(ii) (x – 4) (x – 7) (x – 2) (x + 1) = 16

Solution:

(i) (x – 5) (x + 4) (x – 7) (x + 6) – 504 = 0

(x² – x – 20) (x² – x – 42) – 504 = 0

Put y = x² – x

(y – 20) (y – 42) – 504 = 0

y² – 42y – 20y + 840 – 504 = 0

y² – 62y + 336 = 0

(y – 56) (y – 6) = 0

y = 56 or y = 6

x² – x = 56 or x² – x = 6

x² – x – 56 = 0 or x² – x – 6 = 0

(x – 8)(x + 7) = 0 or (x + 2)(x – 3) = 0

x = 8, -7 or x = 3, x = -2

The roots are 8, -7, 3, -2

(ii) (x – 4)(x – 2)(x- 7)(x + 1) – 16 = 0

(x² – 6x + 8) (x² – 6x – 7) – 16 = 0

Put y = x² – 6x

(y + 8) (y + 7) – 16 = 0

y² – 7y + 8y – 56 – 16 = 0

y² – y – 72 = 0

(y + 9) (y – 8) = 0

y = -9 or y = 8

y = -9 ⇒ x² – 6x = -9

x² – 6x + 9 = 0

(x – 3)² = 0

x = 3, 3

y = 8 ⇒ x² – 6x = 8

x² – 6x – 8 = 0

The roots are 3, 3, 3 ±√17

Question 2.

Solve : (2x – 1) (x + 3) (x – 2) (2x + 3) + 20 = 0.

Solution:

(2x – 1) (2x + 3) (x + 3) (x – 2) + 20 = 0

⇒ (4x^{2} + 6x – 2x – 3) (x^{2} – 2x + 3x – 6) + 20 = 0

⇒ (4x^{2} + 4x – 3) (x^{2} + x – 6) + 20 = 0

⇒ [4(x^{2} + x) – 3] [x^{2} + x – 6] + 20 = 0

Let y = x^{2} + x

⇒ (4y – 3) (y – 6) + 20 = 0

⇒ 4y^{2} – 24y – 3y + 18 + 20 = 0

⇒ 4y^{2} – 27y + 38 = 0

⇒ (4y – 19) (y – 2) = 0

(4y – 19) = 0

4(x^{2} + x) – 19 = 0

4x^{2} + 4x – 19 = 0

or

(y – 2) = 0

x^{2} + x – 2 = 0

(x + 2) (x – 1) = 0

x = -2, +1

The roots are -2, 1, \(\frac{-1 \pm 2 \sqrt{5}}{2}\)

### Samacheer Kalvi 12th Maths Solutions Chapter 3 Theory of Equations Ex 3.4 Additional Questions

Questions 1.

Solve (x – 3) (x – 6) (x – 1) (x + 2) + 54 = 0.

Solution:

(x – 3) (x – 1) (x – 6) (x + 2) + 54 = 0

(x^{2} – 4x + 3) (x^{2} – 4x – 12) + 54 = 0

Put x^{2} – 4x = y

(y + 3)(y – 12) + 54 = 0

y^{2} – 9y – 36 + 54 = 0

y^{2} – 9y + 18 = 0

(y – 3)(y – 6) = 0

Question 2.

Solve the equation (x – 4) (x – 2) (x – 1) (x + 1) + 8 = 0

Solution:

The equation can be rewritten as {(x – 4) (x + 1)} {(x – 2) (x – 1)} + 8 = 0

(x^{2} – 3x – 4)(x^{2} – 3x + 2) + 8 = 0